Hybrid Power Method For Power Supply Of Public Service Computer - Tri Wahyu Supardi; Agus Harjoko (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2018)
Public services require computer-based electricity supply. Not continuous electricity supply in some areas led to a power supply from an alternative power source becomes indispensable. One alternative power source is a solar cell. Solar cell is a sustainable source of electricity but power output is not constant depending on the sunlight. The power source is needed to anticipate the lack of power when the power generated by the solar cell is not enough.In this paper proposed a hybrid design that combines the power supply of electricity from the solar cell, the network provider of electricity, and batteries. This paper discusses methods of hybrid electric power from three sources. Hybrid power is usually done by PCC (Power Controlled Converter), which consists of a controlled power converter for each channel input, but in this study the method proposed hybrid power input specification in the form of a synchronization circuit PCC then replaced by a diode circuit.The design of hybrid power supply in this study resulted in the specification input from the solar cell with Vmp channels (maximum power voltage) 35VDC Voc (open circuit voltage) 43.78VDC, channels of electricity provider with the already converted with SMPS (Switched Mode Power Supply) to 35VDC, and channels of a battery with a minimum voltage of 21VDC maximum 27.6VDC. The test results showed that the implementation of the proposed hybrid method can perform a single capture or hybrid power, and can transfer power between the source retrieval without pause. Implementation of the proposed hybrid method has a 21VDC output voltage range - 43.78VDC and efficiency of 98.6% - 99.5%.